Quiet times with God : 365 little devotions - Thomas, Mack (Sisters, Oregon : Gold 'n' Honey books, 1996)
Quiet times with God helps make daily moments with god a warm, happy experience!
Keywords: Devotional -- Juvenile literature; Inspirational -- Juvenile literature